ENHANCING ACCESS TO JUSTICE THROUGH E-JUDICIARY IN BANGLADESH: A STUDY (UUM Journal of Legal Studies, 2022)
E-judiciary, meaning application of information and communication technologies (ICTs), in justice delivery mechanism is a global phenomenon as inordinate delay in settling disputes resulting in backlogs of cases is one of the common problems in access to justice in almost every judicial system. In Bangladesh, the backlog of cases has become a huge problem, creating a bottleneck in access to justice. Globally, case management is considered an approach appropriate to resolve the problem of delayed justice. Its attraction and utility lie in the ability of the mechanism to provide predictability in the administration of justice. ICTs are now regarded as essential tools for effective case management in addition to delivery of judicial services in an efficient manner. Realising its value as well as benefits, the judiciary of other countries like Australia, Malaysia, and India is using ICTs for reducing the backlog of cases and delivery of justice in an effective way. The countries have already modified their laws as such. To solve Bangladesh’s problem of delayed justice, a project for introducing ICTs in the judiciary has been launched by the Supreme Court of Bangladesh to facilitate prompt and efficient delivery of justice as well as necessary information to the litigants and the public. Hence, this article seeks to highlight the implications of ICTs in the justice delivery mechanism in Bangladesh. This study adopts the qualitative approach of research where primary and secondary data have been gathered from various statutes as well as existing literature. To underline the role of ICTs in making justice accessible, experiences of Australia, Malaysia and India have been shared in this paper. The paper finds that the application of ICTs in the judiciary can make a substantial impact in enhancing access to justice by reducing the backlog of cases. Therefore, the paper recommends that for ensuring access to justice, the application of ICTs in the justice delivery mechanism should be enhanced in Bangladesh.